Managing sand dunes of Thar desert for sand control measures and agriculture - Moharana, P. C.; Pandey, C. B.; Kumar, Mahesh (Indian Farming, 2018)
About 4 lakh ha area under sand dunes was stabilized using various techniques. Sand dune area has reduced by 12% between 1980 and todate. Wind erosion affected area has reduced by 3% of total geographical area of western Rajasthan. Simultaneously, there was change in agricultural land uses in the desert area such as increase in net sown area, total crop area and double crop area and decreasing area under culturable wastelands. These are impacts of combating processes of wind erosion by sand dune stabilization as well as shelterbelt plantation. The models initiated by CAZRI and executed by government departments showed success.